Insight into lithium transport in lithium nitridometallate battery materials from muon spin relaxation - Powell, Andrew S.; Stoeva, Zlatka; Lord, James S.; Smith, Ronald I.; Gregory, Duncan H.; Titman, Jeremy J. (Royal Society of Chemistry, 2013)
Muon spin relaxation and powder neutron diffraction have been combined to study three lithium cobalt nitride battery materials. Neutron diffraction shows that these retain the P6/mmm space group of Li3N with Co located only on Li(1) sites. The lattice parameters vary smoothly with the degree of metal substitution, such that the [Li2N] layers expand while the layer separation contracts, as observed previously for similar series of Cu- and Ni-substituted materials. However, in contrast to the latter, the Li3-x-yCoxN phases exhibit Curie-Weiss paramagnetism and this prevents the use of nuclear magnetic resonance to measure Li+ transport parameters. Therefore, muon spin relaxation has been employed here as an alternative technique to obtain quantitative information about Li+ diffusion. Muon spin relaxation shows that Li+ diffusion in Li3-x- yCoxN is anisotropic with transport confined to the [Li2N] plane at low temperature and exchange between Li(1) and Li(2) sites dominant at high temperature. By a comparison with previous studies some general trends have been established across a range of Cu-, Ni- and Co-substituted materials. For intra-layer diffusion Ea decreases as metal substitution increases and the corresponding expansion of the layers results in a more open pathway for Li+ diffusion. However, an optimal value of x is found with a ≈ 3.69 Å after which the concomitant contraction in layer spacing reduces the polarizability of the lattice framework.